Leveraging B2B field service technicians as a “second sales force”: How service situations affect selling activity and success - Manuel Berkmann; Maik Eisenbeiss; Werner Reinartz; Nico Schauerte (Journal of the Academy of Marketing Science, 2023)
To extract the full revenue potential of their front line, B2B firms use their technical field service force for selling activities. However, as selling is only a complementary activity embedded in technicians' main service tasks, they may struggle to sell effectively. The authors investigate the service situation as a key driver of (i) the technician's decision to engage in selling (selling activity) and (ii) the customer's decision to purchase (selling success). They identify four types of service situations with unique effects on these outcomes. Notably, technicians' selling activity is highest (+0.167em10% compared to baseline) in service situations that offer a lower (-22%) likelihood of success, whereas activity is lower in the most promising situations. Thus, technicians do not properly exploit sales opportunities. The extent of inefficiencies moreover varies by employee-specific moderators, such that specialized technicians and those with little practical experience have particular difficulty exploiting excellent sales opportunities.
Keywords: 330; Service-sales ambidexterity; Service technicians; B2B; Bivariate probit; Heckman selection model